Body mass index and risk of non-alcoholic fatty liver disease: Two electronic health record prospective studies. - Katrina Loomis, A; Kabadi, S; Preiss, D; Hyde, C; Bonato, V; Louis, M; Desai, J; Gill, J; Welsh, P; Waterworth, D; Sattar, N (Endocrine Society, 2015)
The relationship between rising body mass index (BMI) and prospective risk of non-alcoholic fatty liver disease (NAFLD) / non-alcoholic steatohepatitis (NASH) is virtually absent.Determine the extent of the association between BMI and risk of future NAFLD diagnosis, stratifying by sex and diabetes.Two prospective studies using Humedica and THIN with 1.54 and 4.96 years of follow-up respectively.Electronic health record databases Participants: Patients with had a recorded BMI measurement between 15-60kg/m(2), and smoking status, and one year of active status prior to baseline BMI. Patients with a diagnosis or history of chronic diseases were excluded.None Main Outcome Measure: Recorded diagnosis of NAFLD/NASH during follow-up (Humedica ICD-9 code 571.8, and read codes for NAFLD and NASH in THIN).Hazard ratios (HR) were calculated across BMI categories using BMI of 20-22.5kg/m2 as the reference category, adjusting for age, sex and smoking status. Risk of recorded NAFLD/NASH increased linearly with BMI and was approximately 5-fold higher in Humedica (HR=4.78, 95% CI 4.17-5.47) and 9-fold higher in THIN (HR=8.93, 7.11-11.23) at a BMI of 30-32.5 kg/m(2) rising to around 10-fold higher in Humedica (HR=9.80, 8.49-11.32) and 14-fold higher in THIN (HR=14.32, 11.04-18.57) in the 37.5-40 kg/m(2) BMI category. Risk of NAFLD/NASH was approximately 50% higher in men, and approximately double in those with diabetes.These data quantify the consistent and strong relationships between BMI and prospectively recorded diagnoses of NAFLD/NASH and emphasize the importance of weight reduction strategies for prevention and management of NAFLD.